2017
DOI: 10.1111/anae.13834
|View full text |Cite
|
Sign up to set email alerts
|

The added value of cardiac index and pulse pressure variation monitoring to mean arterial pressure-guided volume therapy in moderate-risk abdominal surgery (COGUIDE): a pragmatic multicentre randomised controlled trial

Abstract: There is disagreement regarding the benefits of goal-directed therapy in moderate-risk abdominal surgery. Therefore, we tested the hypothesis that the addition of non-invasive cardiac index and pulse pressure variation monitoring to mean arterial pressure-based goal-directed therapy would reduce the incidence of postoperative complications in patients having moderate-risk abdominal surgery. In this pragmatic multicentre randomised controlled trial, we randomly allocated 244 patients by envelope drawing in a 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 35 publications
1
34
0
1
Order By: Relevance
“…Nonetheless, it is possible that a longer-term follow-up would reveal an effect on postsurgery deaths. 53 The major strength of this study is, unlike recent studies, 59,60 we that have found a significant reduction in moderate-severe postoperative complications in patients who were not at high surgical risk. Identification of the specific patient populations most likely to benefit from GDHT is thus important in future studies.…”
Section: Discussionmentioning
confidence: 78%
“…Nonetheless, it is possible that a longer-term follow-up would reveal an effect on postsurgery deaths. 53 The major strength of this study is, unlike recent studies, 59,60 we that have found a significant reduction in moderate-severe postoperative complications in patients who were not at high surgical risk. Identification of the specific patient populations most likely to benefit from GDHT is thus important in future studies.…”
Section: Discussionmentioning
confidence: 78%
“…2 ) and table (Additional file 2 ). A total of 18 studies (58%) [ 25 , 26 , 28 30 , 32 , 34 , 36 , 38 , 40 , 42 , 44 , 45 , 48 52 ] were judged to carry a low risk of bias (Table 1 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen trials [ 28 , 29 , 31 33 , 35 , 36 , 39 , 41 , 43 , 45 51 ] included patients who were less than 65 years old, and 14 trials [ 3 , 9 , 24 – 27 , 30 , 34 , 37 , 38 , 40 , 42 , 44 , 52 ] included patients who were more than 65 years old. As for the type of alpha-1 adrenergic agonists used in studies, 17 studies [ 3 , 25 , 27 – 30 , 34 38 , 40 , 44 , 45 , 49 – 52 ] selected norepinephrine, 11 studies [ 24 , 26 , 31 33 , 39 , 41 , 42 , 50 , 52 ] considered phenylephrine, 2 studies [ 43 , 46 ] used norepinephrine and phenylephrine, and 1 study [ 9 ] used metaraminol. Additionally, 18 trials [ 3 , 27 – 29 , 31 , 32 , 35 , 37 , 38 , 40 45 , 47 , 48 , 52 ] involved abdominal surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, definitive evidence of benefit has remained elusive, perhaps with the exception of elective high‐risk surgery. The paper by Stens et al in this issue of Anaesthesia adds to the growing number of clinical trials that seem to fail to demonstrate that GDFT has a place in clinical practice . Their study investigated the added value of cardiac index and pulse pressure variation (PPV) monitoring to mean arterial pressure (MAP)‐guided volume therapy in moderate‐risk abdominal surgery.…”
mentioning
confidence: 99%